Compulsory Examination of Homeschoolers in Poland, the Czech Republic, and Slovakia From the Perspective of Parents of Homeschooled Children - Rochovská, Ivana; Droščák, Martin (Pedagogika, 2023)
The research is focused on the issue of compulsory examination of homeschooled children in umbrella schools. Its aim was to find out which variables influence opinions of parents on the process of compulsory examination in an umbrella school and problems in compulsory examination. Pedagogical education of the parents, the number and the age of the homeschooled children do not influence the opinions of the parents on the problems in the compulsory examination in the umbrella school.